Determining the Optimal N Input to Improve Grain Yield and Quality in Winter Wheat With Reduced Apparent N Loss in the North China Plain - Ma, Geng; Liu, Weixing; Li, Shasha; Zhang, Panpan; Wang, Chenyang; Lu, Hongfang; Wang, Lifang; Xie, Yingxin; Ma, Dongyun; Kang, Guozhang (Frontiers in Plant Science, 2019)
Excessive or improper nitrogen (N) application rates negatively affect crop production and thereby environmental quality, particularly for winter wheat production in the North China Plain. Therefore, it is very important to optimize N fertilizer input to balance grain yield, environmental risk, and benefits under irrigated conditions. Three long-term stationary field experiments that included five N levels [0 (N0), 90 (N90), 180 (N180), 240 (N240), and 300 (N300) kg ha-1] were carried out to investigate the effects of N regime on wheat yield, photosynthesis, and N balance at different sites. The grain yield and protein content increased quadratically with N rate, and the maximum values were 8087 kg ha-1 and 13.9% at N application rates of 250 and 337 kg N ha-1, respectively. N application increased the photosynthetic fluorescence parameters (Pn, Gs, and Tr) and N metabolism enzyme activities (NR and GS) which then increased grain yield. With increases in the N rate and advancing experimental years, leaching of soil nitrate into the deeper soil layers (>100 cm) increased. The partial factor productivity (PFPN) was decreased by N because the apparent N loss increased with N application rate. In order to balance grain yield, economic benefit, N use efficiency (NUE), and N loss, the recommended N rate should be 231-246 kg N ha-1, and the corresponding yields and apparent N loss were 8069-8086 ka ha-1 and 59-66 kg ha-1, respectively.